Perancangan Sistem Informasi Pembukuan Sederhana Bagi UMKM - Candra, Arif; Andrew (Journal of Digital Ecosystem for Natural Sustainability, 2022)
There are still many Small and Medium Enterprise (SME) that experience difficulties in developing their business due to lack of access to information and knowledge on how to manage their business properly. Some of the problems that are often encountered include losing proof of transactions, errors when calculating, errors in recording stock, and others. One way to manage finances and inventory well is to do bookkeeping. This research is a qualitative research with a Design Thinking approach. We will add new features to the existing business development information system. We will introduce an inventory management and financial management feature that will help SMEs manage their inventory, record expenses and income more easily and efficiently. By adding new features to the existing business development information system, researchers believe that the business development information system design project in SMEs can help SMEs manage their business better and more effectively.